1965
DOI: 10.4039/ent97239-3
|View full text |Cite
|
Sign up to set email alerts
|

Host-Finding and Repulsion of Aedes aegypti

Abstract: The spontaneous activation of Aedes aegypti, and their responses to external stimuli (especially changes in temperature, humidity and carbon dioxide concentration) have been analyzed in a way that allows the controlling neural mechanisms to be inferred. In general, the flying insect turns back on leaving a favorable air stream, but does not turn on entering one. The normal attack program reduces to four basic steps: a general search initiated by a small rise in the CO2 level, no turn when the insect enters the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 11 publications
4
44
0
Order By: Relevance
“…The ability of CO2 alone to act as a mosquito attractant has been well documented in a number of behavioral investigations (Roth and Willis, 1952;Daykin et al, 1965). Acree et al (1968) reported that COz was an attractant when tested in combination with L-LA, but reported that neither was effective when tested separately under their conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CO2 alone to act as a mosquito attractant has been well documented in a number of behavioral investigations (Roth and Willis, 1952;Daykin et al, 1965). Acree et al (1968) reported that COz was an attractant when tested in combination with L-LA, but reported that neither was effective when tested separately under their conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Upwind turning in odour plumes also has been recorded for tsetse and stable flies (Colvin et al, 1989;Paynter and Brady, 1993;Schofield and Brady, 1997) in response to CO 2 , octenol and acetone odours. In a different bioassay setup using vertical, odour-laden convection currents, Daykin et al (1965) reported increased turning of Ae. aegypti when leaving but not when entering a skin-odour plume.…”
Section: Track Anglementioning
confidence: 99%
“…most attractants and activators), and close range (<1·m) if sensed near the host (e.g. cues inducing landing and biting; Daykin et al, 1965;Gillies, 1980;Sutcliffe, 1987;De Jong and Knols, 1995;Dekker et al, 1998). For hematophagous insects, CO 2 is generally considered to be an attractant only when close to the host (e.g.…”
Section: Sensitivity To Skin Odour and Comentioning
confidence: 99%
“…When mosquitoes are not subject to stimuli, it is possible to assume that they move randomly in any direction [9]. This leads to a diffusion equation which can be extended to take into account the landscape heterogeneity or correlated random walk.…”
Section: The Mathematical Modelmentioning
confidence: 99%